Compatibilizing and reinforcing an immiscible blend based on poly(lactic acid) with delaminated graphite: From raw graphite to enhanced polymer mechanical properties - Nopparat Komrapit (2018)
© 2018 Wiley Periodicals, Inc. The centrifugation–filtration method is widely applied to the delamination of layered fillers for polymer reinforcement. However, it is a time-consuming, multistep procedure and offers low product yield. In this study, a simple mechanical grinding process was used as a delamination method for raw graphite. For the first time, without centrifugation and the removal of the graphite precipitate, the incorporation of the entire ground graphite obtained from the grinding process into a poly(lactic acid) (PLA)–poly(butylene adipate-co-terephthalate) (PBAT) immiscible blend was capable of improving the polymer mechanical properties. The composites obtained displayed an enhancement of either the ductility or strength, depending on the loaded ground graphite content. The blend films uniquely exhibited an enhanced elongation at break because of the PLA–PBAT compatibilizing role of the delaminated graphite at a low loading (0.1 phr). With the higher content of ground graphite (0.5–3 phr), the Young's modulus of the blend increased to achieve the value predicted by the Halpin–Tsai equation. Mechanical grinding required only a small amount of delamination medium without the aid of surfactants and harsh preparation conditions and, thus, was promisingly simple, cost effective, general, high yield, and practically scalable. The use of a low filler content rendered it potentially extendable to the delamination of other layered fillers available in limited amounts for high-mechanical-performance polymer composites. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46821.